2010
DOI: 10.1016/j.neuropsychologia.2009.09.031
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA and CLSTN2 polymorphisms exert interactive effects on human episodic memory

Abstract: a b s t r a c tIndividual differences in episodic memory are highly heritable. Several studies have linked a polymorphism in the gene encoding the KIBRA protein to episodic memory performance. Results regarding CLSTN2, the gene encoding the synaptic protein calsyntenin 2, have been less consistent, possibly pointing to interactions with other genes. Given that both KIBRA and CLSTN2 are expressed in the medial temporal lobe and have been linked to synaptic plasticity, we investigated whether KIBRA and CLSTN2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 78 publications
(131 reference statements)
5
65
3
Order By: Relevance
“…Behaviorally, we confirmed previous findings of increased episodic memory performance in KIBRA T carriers (Papassotiropoulos et al, 2006;Bates et al, 2009;Preuschhof et al, 2010;Vassos et al, 2010). For the brain imaging data, Papassotiropoulos et al (2006) reported enhanced hippocampal activation in noncarriers of the T allele, but here, a genotype effect on hippocampal activation was seen in the opposite direction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Behaviorally, we confirmed previous findings of increased episodic memory performance in KIBRA T carriers (Papassotiropoulos et al, 2006;Bates et al, 2009;Preuschhof et al, 2010;Vassos et al, 2010). For the brain imaging data, Papassotiropoulos et al (2006) reported enhanced hippocampal activation in noncarriers of the T allele, but here, a genotype effect on hippocampal activation was seen in the opposite direction.…”
Section: Discussionsupporting
confidence: 90%
“…The T allele of a common KIBRA (WW and C2 domain containing 1) C/T polymorphism (rs17070145) was first linked to increased episodic memory performance in a genomewide association study and two independent replication samples by Papassotiropoulos and colleagues (2006). In subsequent studies, the T allele has been associated with increased episodic memory performance (Bates et al, 2009;Preuschhof et al, 2010;Vassos et al, 2010; but see Need et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The two SNPs were in Hardy-Weinberg equilibrium in both cohorts and the allele frequencies (Table 3) were similar to other Caucasian populations (e.g., Preuschhof et al, 2010).…”
Section: Genotypingsupporting
confidence: 70%
“…Given that complex phenotypes, such as memory, draw on multiple neurobiological substrates and are thus influenced by multiple genes (e.g., Bertolino et al, 2006;Markett et al, 2011;Nagel et al, 2008;Preuschhof et al, 2010), it is imperative to further investigate the resource-modulation hypothesis in relation to gene-gene interactions. Based on this consideration, and in light of the age-related decline in various preand postsynaptic components of the DA system (for reviews, see Bäckman et al, 2006Bäckman et al, , 2010, we investigated (i) whether genes relevant to pre-and postsynaptic components of the DA system contribute interactively to individual differences in episodic memory performance; and (ii) whether such interactive effects are magnified in old age.…”
Section: Introductionmentioning
confidence: 99%